The Sense of Gender Equality in Papuans’ Philosophy - Kristina Sawen (Fakultas Hukum Universitas Hang Tuah, 2017)
The construct of gender in social life manifests onto its discrimination in every aspect of society. Women have a weak position and thus, become a “weapon” to weaken their own development in this growing emancipation era. Some legal efforts and the theory of feminist have developed to advocate them to grow up and get involved in various aspects of development; at least, it may suppress the level of discrimination toward women. Implementing the theory of feminism, however, should understand and see through some values that exist in society, as in Papuan women‟s life. In the context of kinship, it may tie and harmonize the family bond. Therefore, the theory of feminism can be well implemented and accepted in a society which is full of togetherness, kinship, relatives, and love values.